HBR guide to executing your strategy - Vertullo, Jon; DeWard, Erin (Harvard business review guides., 2023)
Put your strategy into action. Even the best competitive strategies mean nothing if they can't be executed. Yet many organizations struggle when they move from defining a strategy to implementing it. Somehow, all the careful planning falls to the side, and leaders are left wondering how to pick up the pieces. The HBR Guide to Executing Your Strategy is here to help. This book offers leaders and managers tips and advice for how to take even the most detailed strategy and apply it throughout their organizations. You'll learn how to: get employees on board with a new strategy; communicate plans effectively; identify milestones for progress toward objectives; eliminate initiatives that no longer contribute; overcome naysayers and resistance; avoid execution traps; and adjust course where necessary. Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.